SNPs in SNCA, MCCC1, DLG2, GBF1 and MBNL2 are associated with Parkinson's disease in southern Chinese population. Issue 15 (11th July 2020) - Zhao, Aonan; Li, Yuanyuan; Niu, Mengyue; Li, Guanglu; Luo, Ningdi; Zhou, Liche; Kang, Wenyan; Liu, Jun
Abstract: Numerous single nucleotide polymorphisms (SNPs), which have been identified as susceptibility factors for Parkinson's disease (PD) as per genome‐wide association studies, have not been fully characterized for PD patients in China. This study aimed to replicate the relationship between 12 novel SNPs of 12 genes and PD risk in southern Chinese population. Twelve SNPs of 12 genes were detected in 231 PD patients and 249 controls, using the SNaPshot technique. Meta‐analysis was used to assess heterogeneity of effect sizes between this study and published data. The impact of SNPs on gene expression was investigated by analysing the SNP‐gene association in the expression quantitative trait loci (eQTL) data sets. rs8180209 of SNCA (allele model: P = .047, OR = 0.77; additive model: P = .047, OR = 0.77), rs2270968 of MCCC1 (dominant model: P = .024, OR = 1.52), rs7479949 of DLG2 (recessive model; P = .019, OR = 1.52), rs10748818 of GBF1 (additive model: P < .001, OR = 0.37), and rs4771268 of MBNL2 (recessive model: P = .003, OR = 0.48) were replicated to be significantly associated with the increased risk of PD. Noteworthy, a meta‐analysis of previous studies suggested rs8180209, rs2270968, rs7479949 and rs4771268 were in line with those of our cohort. Our study replicated five novel functional SNPs in SNCA, MCCC1, DLG2, GBF1 and MBNL2 could be associated with increased risk of PD in southern Chinese population.